PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PERAWAT RUMAH SAKIT (Studi Kasus Pada RS. HKBP Balige, Kabupaten Toba Samosir, Sumatera Utara) - Sinaga, Dewi Siska; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the effect of work stress and work environments on job satisfaction of nurses Hospital Balige HKBP. Where the proposed two independent variables and the dependent variable, namely the stress of work and the working environment act as the independent variable and job satisfaction act as the dependent variable.The population in this study were nurses HKBP Balige Hospital, with sampling amounted to 53 people with slovin formula. Search procedures performed by accidental sampling. The research data in the form of primary data, with the questionnaire as a research instrument, data analysis used is menggunakanan statistical analysis with SPSS.Results of analysis using multiple linear regression, t test and f test so it can be seen that the work stress variables negatively affect the job satisfaction of nurses (H1), that the work environment a significant effect on job satisfaction of nurses (H2), and a significant relationship between work stress and the work environment to nurse job satisfaction (H3).Keywords : Work Stress, Work Environment and Job Satisfaction